Physiotherapy treatment of urinary stress incontinence in women. Part 2 - Kwaśna, Krystyna; Chmielewska, Daria; Piecha, Magdalena; Halski, Tomasz; Taradaj, Jakub; Juras, Grzegorz; Skrzypulec-Plinta, Violetta (Menopause Review/Przegląd Menopauzalny, 2012)
Nowadays, modern and more attractive methods of conservative treatment of urinary stress incontinence are sought. Authors’ attention has focused on vibration training which is a new form of rehabilitation and fitness. Fitness centers, training rooms and rehabilitation centers are equipped with vibration platforms. The literature reports an increase in muscle strength and mechanical power as a result of vibration training. There are scientific rationales for assuming a positive impact of this form of training on the pelvic floor muscles. However, this aspect requires verification. Electrical stimulation is a conventional method of treatment of urinary stress incontinence. There has been good evidence for effectiveness of electrotherapy in strengthening of the pelvic floor muscles. The possibility of applying these methods depend on the age and general physical condition of women with urinary stress incontinence.